Syncretism in Miao Healing: Bridging Shamanic Practices and Scientific Treatments with Religion, Ritual, and Local Knowledge - Chen, Zhengfu (Religions, 2024)
The Miao (Hmong) community in Southwest China, deeply entrenched in a religious belief system acknowledging the omnipresent spiritual essence and venerating ancestor worship, perceives life as a harmonious blend of the “soul” and the “body”, intricately interwoven and mutually reinforcing. Within this cultural milieu, shamanism and healing practices form an inseparable nexus, epitomizing a worldview characterized by the harmonious coexistence of gods, spirits, ancestors, ghosts, and shamans. This study scrutinizes the syncretism employed by the Miao to address illness, bridging shamanic practices and scientific treatments with religion, ritual, and local knowledge. Through methodologies such as autoethnography, participant observation, and in-depth interviews, the research explores a Miao woman’s healing journey, synthesizing shamanic traditions with scientific interventions to reveal the nuanced interplay between traditional customs, environmental influences, and health beliefs. Despite encountering challenges like limited healthcare access and high costs, numerous Miao people seek assistance from shamans, underscoring the community’s resilience in navigating the intricate interrelationship between traditional practices and modern healthcare systems. By emphasizing the significance of syncretism, this study contributes to a nuanced understanding of how the Miao seamlessly integrate shamanic practices with scientific treatments, fostering improved intercultural communication and cultivating culturally sensitive healthcare practices, ultimately enhancing the overall well-being of the Miao community.